Actividad tripanocida y citotóxica de extractos de plantas colombianas (2011)
ABSTRACT: Introduction. The treatment of Chagas disease is based on only two drugs with limited efficacy and significant side effects. The rich biodiversity of the Colombian flora makes bio-prospecting a potential alternative in the search for new antiparasitic drugs. Objective. Potential trypanocidal activity and cytotoxicity was assessed in extracts from 23 Colombian plants.Materials and methods. Extracts of leaves, stems, or of the whole plants were obtained in solvents of a range of polarities. The activity against Trypanosoma cruzi epimastigotes and the cytotoxicity were evaluated by the MTT enzymatic micro-method. Extracts active against epimastigotes and with low cytotoxicity were also tested on trypomastigotes and intracellular amastigotes. Results. Among the extracts, biological activity was confirmed in 4 species. The extracts were active on epimastigotes and trypomastigotes; one was active also against amastigotes. The latter extract was isolated from the plant Hieronyma antioquensis and presented IC50 of 3.1 mg/ml for epimastigotes, 11.5 mg/ml for trypomastigotes and 2.9 mg/ml for amastigotes. The selectivity indexes were 25, 7, and 27 respectively.